A bi-level mathematical model to protect gateways in underwater wireless sensor networks. (12th October 2022) - Maleki, Zahra; Maleki, Hamid Reza; Akbari, Reza
Since energy resources in underwater wireless sensor networks (UWSNs) are limited and non-renewable, energy efficiency in these networks is essential. Jamming attacks are the most common denials of service attacks in UWSNs that increase the amount of energy consumption. In this paper, a bi-level model for the protection of gateways in underwater sensor networks is introduced. In this model, the attacker intends to increase the network's energy consumption by placing a determined number of jammers on the gateways; hence, the network manager wants to assign anti-jamming techniques to a subset of gateways to protect them against these attacks. The efficiency of this model in reducing energy consumption after a jamming attack is shown in several instances. These instances are solved with hybridisation from genetic, simulated annealing, and dragonfly algorithms with CPLEX solver, and their performances are evaluated with the two-sample t-test.